Self-affirmation and False Allegations: The Effects on Responses to Disclosures of Sexual Victimization - Roos, Melissa S. de (Journal of interpersonal violence, 2022)
The rise of the #MeToo movement highlights the prevalence of sexual victimization and gives a voice to victims who may have been silent before. Nevertheless, survivors or victims of sexual violence who come forward may be blamed or not believed. These reactions are evident both with adult and child victims. Further, fears about false accusations of sexual misconduct may negatively impact responses to disclosures. This study aimed to examine gender differences in perceptions toward the #MeToo movement, and the extent to which these translate into a skeptical response to disclosure. Further, we wanted to explore whether proximity to false allegations of sexual violence was linked with more negative responses and whether use of self-affirmations may decrease the likelihood of such a response. Through an online survey (N = 235) on Amazon?s Mechanical Turk, we assessed participants? exposure to and perceptions of the #MeToo movement. Further, we asked them about their proximity to sexual violence (victimization or perpetration) and to false allegations. Using a threat manipulation (news article about false accusation) and a self-affirmation exercise, we studied the effects of both variables on responses to disclosure. Results indicated that after reading an article about a false accusation, male participants were more likely to blame a victim of childhood sexual abuse and to perceive the abuse as less harmful, compared with female participants. Further, we found that self-affirmation was linked with more supportive responses to a disclosure. These findings highlight the threatening nature of false accusations of sexual violence for men, and how this threat may shape the narrative regarding sexual violence. Opportunities to use self-affirmation to change this narrative to a more supportive one are discussed.